PENATALAKSANAAN TEKNIK PEMERIKSAAN CT-BRAIN DENGAN INDIKASI VERTIGO CENTRAL DI UNIT RADIOLOGI RUMAH SAKIT AWAL BROS AHMAD YANI PEKANBARU - M.Hafizh Hermawan (LPPM Universitas Awal Bros, 2024)
Vertigo is a common complaint found in clinical practice. The lifetime prevalence rate of vertigo in adults aged 18-79 years reaches 7.4% with an annual incidence rate of 1.4%. The incidence rate is higher in women than men.Vertigo is a symptom characterized by a feeling of change in the position of the body or the position of the surrounding environment. Based on the location of the cause, vertigo is divided into central and peripheral vertigo. Central vertigo is vertigo caused by diseases originating from the central nervous system. The causes of central vertigo can vary. Some of these are vestibular migraine, vertebrobasilar ischemic stroke, TIA (Transient Ischemic Attack), multiple sclerosis, or tumors located in the cerebellopontine angle and congenital disorders such as Dandy Walker Syndrome. One imaging modality that can diagnose this is Computed Tomography or commonly called CT-Scan. CT-Scan is a process that uses digital processing to produce a three-dimensional internal image of an object from a series of X-rays which produces a two-dimensional image. Head CT-Scan examinations are quite numerous and routinely carried out by almost every Radiology unit that provides CT-Scan services. According to the parameters used must be in accordance with the pathological abnormality, namely by using one range with a slice thickness of 7-10 mm from Basis Cranii up to Vertex.